Can physical exercise improve venous function in the context of chronic venous diseases? The impact of sport on varicose veins of the lower limbs - a review - Salwa, Adam; Gajdzińska, Natalia; Rostkowska, Weronika; Rutkowski, Wojciech; Rzepka, Maciej; Sztuba, Karolina; Puchała, Justyna; Rymaszewska, Katarzyna; Starzomska, Dominika; Basiura, Karolina (Quality in Sport, 2024)
Introduction: Varicose veins, a common form of chronic venous disease, arise from the dysfunction of veins in the lower limbs due to increased pressure and impaired blood flow. Regular physical activity and a balanced diet are crucial in managing and potentially improving symptoms of this condition. Material and methods: We have gathered the available materials and scientific reports, analyzing and summarizing them in a single study. Aim of study: We aimed to evaluate how physical activity and lifestyle changes impact the progression and management of varicose veins and chronic venous disease. Conclusion: The study underscores the significant role of physical activity and lifestyle changes in managing varicose veins and chronic venous disease. By enhancing calf muscle function and improving venous blood flow, these interventions can help reduce symptoms, prevent disease progression, and potentially decrease the need for surgical treatments.